The Effect of Progressive Muscle Relaxation Exercises Applied to Caregivers of Palliative Care Patients on Stress Coping Styles and Anxiety Levels: A Randomised Controlled Trial - Turan, Guelcan Bahcecioglu; Oezer, Zuelfinaz; Demir, Cuma (Wiley, 2025)
Objective: This study aimed to investigate the effect of progressive muscle relaxation exercises on the ability to cope with stress and anxiety level in caregivers of palliative care patients. Design: The study was conducted as a single-blind study with pretest-posttest randomised control group. Method: The study was conducted between May 11 and July 22, 2021. The caregivers in the experimental group were asked to perform a total of 28 sessions of progressive muscle relaxation exercise for 30 min a day for 4 weeks. No interventions were made in the control group during the study. Data were collected using the 'Caregiver Information Form,' 'State-Trait Anxiety Inventory (STAI)' and 'Stress Coping Styles Scale (SCSS).' Number and percentage, mean, standard deviation, Chi-Square Test, independent groups t-test, dependent groups t-test, Mann-Whitney U Test, Wilcoxon Signed Rank Test and simple linear regression analysis were used to summarise the data obtained from the study. Results: A total of 66 caregiver patient relatives, 33 in the experimental group and 33 in the control group, were included in the study. When the posttest mean scores of caregivers in the experimental and control groups were compared, it was found that the experimental group's STAI and negative SCSS subscale mean scores decreased compared to the control group's mean scores, while the positive SCSS subscale mean scores increased, and the difference was statistically significant (p < 0.05). It was found that the variable of progressive muscle relaxation exercise had a negative effect on anxiety (beta = -0.962), helpless approach (beta = -0.535) and submissive approach (beta = -0.643), while it had a positive and significant effect on seeking social support (beta = 0.765), self-confident approach (beta = 0.832) and optimistic approach (beta = 0.493) (p < 0.001). Conclusion: It was found that after progressive muscle relaxation exercises, the anxiety of caregivers of palliative care patients decreased, the use of positive stress coping methods increased and the use of negative stress coping techniques decreased. Patient or Public ContributionIt is not necessary.
Keywords: anxiety; caregiver; palliative care; progressive muscle relaxation; stress